Peran Guru Sekolah Dalam Menemukan Minat Dan Bakat Siswa Di Sekolah - Ainul Mardiyah; Ihsan Zamzami Banurea; Fahman Al-Hanafi Kudadiri (GLOBAL SCIENTS PUBLISHER, 2026)
Interests and talents are important potentials that need to be identified and developed from an early school age so that students can grow optimally. Teachers have a strategic role in discovering students’ interests and talents due to their intensive interaction with students in daily learning activities. This study aims to examine the role of school teachers in identifying students’ interests and talents in the school environment. The research employed a descriptive qualitative approach, with data collected through semi-structured interviews with teachers directly involved in the teaching and learning process. In addition, this study was supported by a literature review of developmental psychology books and relevant Indonesian national journals. The findings indicate that teachers play a significant role in identifying students’ interests and talents through observation of learning behaviors, direct communication, and students’ participation in academic and extracurricular activities. Teachers’ understanding of students’ developmental characteristics and individual differences is a key supporting factor in this process. However, teachers still face several challenges, such as limited time, large class sizes, and curriculum demands. This study concludes that optimizing the role of teachers in identifying students’ interests and talents requires strong support from the school system to ensure holistic and sustainable student development.